2009
DOI: 10.1654/4356.1
|View full text |Cite
|
Sign up to set email alerts
|

Nagmia rodmani n. sp., Nagmia cisloi n. sp., and Probolitrema richiardii (López, 1888) (Gorgoderidae: Anaporrhutinae) from Elasmobranchs in the Gulf of California, Mexico

Abstract: The generic diagnosis of Nagmia Nagaty, 1930, is emended to include species having some vitelline follicles extending into the extracecal space. Two new species belonging in the genus are described from the Gulf of California: Nagmia rodmani n. sp. from the body cavity of the giant electric ray, Narcine entemedor Jordan and Starks, 1895, and Nagmia cisloi n. sp. from the body cavity of the smoothtail mobula, Mobula thurstoni (Lloyd, 1908). Both species are distinguished from each other and the 13 other known c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…The specimens described here agree well with the diagnostic morphological characters of the genus Anaporrhutum as described by Curran et al (2003) and Campbell (2008). In particular, the main characters used for their identification as belonging to Anaporrhutum were the caeca without diverticula, the testicular follicles traversing the caeca, the vitellaria medial or ventral to the caeca, and the H-shaped excretory vesicle.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…The specimens described here agree well with the diagnostic morphological characters of the genus Anaporrhutum as described by Curran et al (2003) and Campbell (2008). In particular, the main characters used for their identification as belonging to Anaporrhutum were the caeca without diverticula, the testicular follicles traversing the caeca, the vitellaria medial or ventral to the caeca, and the H-shaped excretory vesicle.…”
Section: Discussionsupporting
confidence: 84%
“…Anaporrhutum mundae sp. nov. most closely resembles A. euzeti, which was described from the Gulf of California (Mexico) in Myliobatis longirostris Applegate & Fitch, Narcine entemedor Jordan & Starks, Hypanus dipterurus (Jordan & Gilbert) and Urobatis maculatus Garman (Curran et al 2003). However, A. mundae sp.…”
Section: Remarksmentioning
confidence: 84%
See 2 more Smart Citations
“…Five valid species of Acanthobothrium have been reported worldwide from three species of Narcine (Table 5) (Subhapradha, 1955; Goldstein et al 1969; Brooks and Mayes 1978; Marques et al 1997b), but no species of Acanthobothrium in Narcine have been reported from Mexico (Merlo-Serna and García-Prieto 2016). In Mexico, only two species of helminth have been reported previously from Narcine : Anaporrhutumeuzeti Curran, Blend & Overstreet, 2003 and Nagmiarodmani Curran, Blend & Overstreet, 2009 (Curran et al 2003; Curran et al 2009).…”
Section: Discussionmentioning
confidence: 99%